Cultural factors influencing Japanese nurses' assertive communication: Part 2 - hierarchy and power - Mieko Omura (2018)
© 2018 John Wiley & Sons Australia, Ltd. Hierarchy and power characterize health-care relationships around the world, constituting a barrier to assertive communication and a risk to patient safety. This issue is more problematic and complex in countries such as Japan, where deep-seated cultural values related to hierarchy and power persist. The current paper is the second of two that present the findings from a study exploring Japanese nurses' views and experiences of how cultural values impact assertive communication for health-care professionals. We conducted semistructured interviews with 23 registered nurses, following which data were analyzed using directed content analysis. Two overarching themes emerged from the analysis: hierarchy/power and collectivism. In the present study, we focus on cultural values related to hierarchy and power, including differences in professional status, gender imbalance, seniority/generation gap, bullying, and humility/modesty. The findings from our research provide meaningful insights into how Japanese cultural values influence and constrain nurses' communication and speaking up behaviors, and can be used to inform educational programs designed to teach assertiveness skills.